Fabrication and Characterization of Matrix-Type Transdermal Patches Loaded with Ramipril and Repaglinide Through Cellulose-based Hydrophilic and Hydrophobic Polymers: In Vitro and Ex Vivo Permeation Studies. Issue 16 (2nd November 2017) - Zaman, Muhammad; Khalid, Usman; Abdul Ghafoor Raja, Maria; Siddique, Waqar; Sultana, Kishwar; Amjad, Muhammad Wahab; Ur Rehman, Atta; Ahmad Khan, Mahtab
ABSTRACT: Transdermal patches loaded with ramipril and repaglinide were prepared with the ambition to develop matrix-type transdermal drug delivery system for enhanced permeability and hence improved bioavailability. Different formulations were designed by intermittent concentrations of hydroxypropyl methylcellulose K4M as hydrophilic polymer and ethyl cellulose as hydrophobic polymer. Solvent casting method was used for the fabrication of transdermal patches. Oleic acid and propylene glycol were used to enhance permeability along with polyethylene glycol 400 as plasticizer. Newly designed patches were then evaluated for various physicochemical and mechanical properties. Compatibility studies were performed by Fourier transformed infrared spectroscopy which did not reveal any interaction between drug and polymers. Crystalline nature of drugs was confirmed when they were subjected to X-ray diffraction study and surface morphological studies using scanning electron microscopy. Transdermal patches were of good mechanical strength with folding endurance of more than 300-fold and 100% flatness. Percent drug contents of ramipril and repaglinide ranged from 90 to 105%, i.e., analogous to official limits. In vitro and ex vivo permeation studies were executed using franz diffusion cell. The cumulative amount of drug permeated through skin was 55.22–112.72% for repaglinide and 73.14–91.46% for ramipril. The release behavior of the permeated drug was analyzed by the application of model-dependent approaches. The results showed that Korsmeyer–Peppas model was found to be dominating in most of the formulations and drugs followed diffusion mechanism. It could be concluded that hydroxypropyl methylcellulose K4M and ethyl cellulose has great potential for ramipril and repaglinide as a vector for transdermal drug delivery effectively because of the formation of smooth surfaces of patches, high folding endurance, and entrapment efficiency with the ability to release the drugs in sustained manner. GRAPHICAL ABSTRACT: